Translation into Portuguese language (Brazil), transcultural adaptation and validation of the quality of life questionnaire in female pattern hair loss (WAA-QoL-BP) - Machado Shimizu, Gisele Keiko; Wedy, Glaucia Ferreira; Schaefer, Luiza Vasconcelos; Ramos, Paulo Mueller [UNESP]; Miot, Helio Amante [UNESP] (Soc Brasileira Dermatologia, 2018)
BACKGROUND: Female pattern hair loss (FPHL) is a common complaint in adult women and inflicts major impact in quality of life, however, there is no specific questionnaire available in Portuguese for such evaluation. OBJECTIVES: Translation into Brazilian Portuguese, cultural adaptation and validation of the WAA-QoL (Women's Androgenetic Alopecia Quality of Life Questionnaire). METHODS: Methodological study. After authorization by the author, cultural (linguistic) translation and adaptation to Portuguese of the WAA-QoL questionnaire were carried out. The translated version (WAA-QoL-BP) and DLQI (Dermatology Life Quality index) were submitted to patients with FPHL for concurrent validation. Twenty patients were reevaluated to assess temporal stability. RESULTS: A total of 116 patients with APF were evaluated, the mean age (SD) was 47 (14) years, and 89 (76%) patients were classified as grades II and III (Sinclair). There was high internal consistency: Cronbach's alpha was 0.97 for the WAA-QoL-BP and 0.87 for the DLQI. The correlation between WAA-QoL and DLQI resulted in (rho) 0.81 (p <0.01). The intraclass correlation coefficient for complete agreement of WAA-QoL-BP was 0.95 (p <0.01) in the test-retest comparison. STUDY LIMITATIONS: Sampling of patients only from the State of Sao Paulo. CONCLUSIONS: A Brazilian version for WAA-QoL was translated and adapted, which proved to be valid and consistent.
Keywords: Alopecia; Health impact assessment; Indicators of quality of life; Quality of life; Sickness impact profile; Surveys and questionnaires; Validation studies; Women